Enhancement of the predictive power of molecular dynamics simulations for the determination of self-diffusion coefficient and viscosity demonstrated for propane - Higgoda, Ubaya; Hellmann, Robert; Koller, Thomas Manfred; Fröba, Andreas Paul (Fluid Phase Equilibria, 2019)
For the development and optimization of classical effective force fields (FFs) commonly used in molecular dynamics (MD) simulations, often experimental data are required. An alternative fully-predictive approach is the use of simplified pair-specific, ab initio-based FFs (AI-FFs) derived from quantum calculations in the limit of zero density. This approach, which could successfully be employed in our recent work for methane (CH4) and carbon dioxide (CO2), has not been investigated for relatively large systems including propane (C3H8). In the present study, C3H8 was selected as model system to evaluate the predictive power of MD simulations with respect to the determination of the self-diffusion coefficient and viscosity. For this aim, a semi-rigid version of our new simplified all-atom AI-FF was applied over a broad density range from the superheated vapor to the gas state and supercritical region up to the compressed liquid state. To elucidate the effects of the AI-FF on the calculated dynamical properties of C3H8, corresponding MD simulations representing the first investigations for the studied thermodynamic states were also performed using commonly employed, effective literature FFs in the form of TraPPE and OPLS. With the exception of the compressed liquid state, it was found that our ab initio-based approach improves the prediction results for the self-diffusion coefficient and viscosity at the studied thermodynamic states corresponding to pressures between (0.1 and 5) MPa and temperatures between (293.15 and 403.15) K compared to the use of effective FFs. This could be demonstrated by comparison with the ab initio-based calculations at the limit of zero density and the scarce experimental data. It could be figured out that the combination of an all-atom and a rigid or semi-rigid representation in our ab initio-based FFs for C3H8 as well as CH4 and CO2 suits well for a reliable simulation of dynamical properties over a broad density range.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Ab initio calculation; Molecular dynamics simulation; Propane; Self-diffusion coefficient; Viscosity

Fick diffusion coefficients of binary fluid mixtures consisting of methane, carbon dioxide, and propane via molecular dynamics simulations based on simplified pair-specific ab initio-derived force fields - Higgoda, Ubaya; Hewa Kankanamge, Chathura Jayan Kankanamge; Hellmann, Robert; Koller, Thomas Manfred; Fröba, Andreas Paul (Fluid Phase Equilibria, 2019)
For the calculation of thermophysical properties of fluids with molecular dynamics (MD) simulations, effective force fields (FFs) which are optimized against experimental vapor-liquid equilibria are often used. Examples for this FF category are TraPPE, OPLS, and AMBER. An alternative are simplified pair-specific, ab initio-based FFs (AI-FFs), which are derived from quantum-chemical calculations in the limit of zero-density in combination with the kinetic theory of gases, and, thus, feature a predictive character. In the present study, we show with the help of selected binary fluid mixtures that the predictive power of MD simulations in calculating Fick diffusion coefficients can be improved using simplified pair-specific AI-FFs based on corresponding FFs for the pure substances. To evaluate the performance of the new AI-FFs in comparison with the TraPPE FFs, binary mixtures consisting of methane, carbon dioxide, and propane were investigated from the superheated vapor to the gas state and supercritical region up to the compressed liquid state. For the determination of the Fick diffusion coefficient at pressures between (0.1 and 12) MPa, temperatures between (293 and 355) K, and mole fractions between 0.05 and 0.95, separate simulations for the analysis of the Maxwell–Stefan diffusion coefficient and the thermodynamic factor were performed considering system size effects. With the exception of the compressed liquid state and regions in vicinity of the two-phase boundary, where the TraPPE FFs are generally superior, the AI-FFs show improved predictions for the Fick diffusion coefficient with average expanded statistical uncertainties of 12%. This could be demonstrated by comparison of the simulation results with the theoretical ab initio calculations and the available experimental data, resulting in average absolute deviations of 7% and 13% for the AI-FFs and TraPPE FFs.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Ab initio calculations; Binary mixtures; Carbon dioxide; Fick diffusion coefficient; Methane; Molecular dynamics simulation; Propane

Self-diffusion coefficient and viscosity of methane and carbon dioxide via molecular dynamics simulations based on new ab initio-derived force fields - Higgoda, Ubaya; Hellmann, Robert; Koller, Thomas Manfred; Fröba, Andreas Paul (Fluid Phase Equilibria, 2019)
In the present study, the self-diffusion coefficient and viscosity of methane (CH4) and carbon dioxide (CO2) were studied by molecular dynamics (MD) simulations in the superheated vapor, gaseous, and supercritical state. The parameters used for the MD simulations are based on new molecular force fields (FFs), which were derived from previously developed, highly accurate pair potentials based on ab initio-calculated interaction energies in the limit of zero density. Using these optimized rigid all-atom FFs, multiple MD simulation runs in the order of several mu s were performed to evaluate the dynamic viscosity from the plateau of the time integral of the pressure autocorrelation function and the self-diffusion coefficient from the linear Einstein regime. For the latter property, it is shown that the Yeh-Hummer correction accounting for effects of the finite box size for dense liquid systems in the hydrodynamic regime can be transferred consistently to gaseous systems at various densities. A comparison of the simulated dynamical properties obtained from our ab initio-derived FFs with those obtained from established literature FFs showed that our suggested approach is superior to the other rigid all-atom approaches and in particular to flexible and united-atom models over density ranges corresponding to pressures between 0.1 and 10 MPa. For temperatures of 295, 325, and 355 K, our simulation results for the product of self-diffusion coefficient and density as well as for the dynamic viscosity with average expanded statistical uncertainties (k = 2) of 0.6% as well as 8.0%, respectively, represent the density dependency of both properties and agree with the few simulation and experimental data available in the literature. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; Methane; Molecular dynamics simulation; Self-diffusion coefficient; Viscosity